User Interface and User Experience Design of "PAWTEL" Mobile Application for Finding Pet Boarding Services - Fiqri Andany Nurul Firdaus; Pratama Bayu Widagdo (Gorga : Jurnal Seni Rupa, 2025)
Searching for pet boarding services is very necessary for pet owners when they have an urgent need. One solution to make it easier for users to find and order boarding services is the design of the Pawtel mobile application interface through a design thinking approach. This approach is oriented towards the needs of users and the various difficulties faced with a product or service. The data collection method is observational, an online survey, and an interview with qualitative analysis methods that adjust to each stage of design thinking. The results of brainstorming ideas at the ideate stage were sorted using the Eisenhower Matrix, then designing information architecture and flowcharts as materials for designing wireframes and prototypes using Figma. The resulting prototype was tested on 15 testers through Maze, with testing results showing that the appearance and key features of the Pawtel app were excellent. The use of gamification elements in the creation of pet avatars has also been proven to provide an interactive experience and attract users' attention. The test results from Maze show that Maze's usability score is 82, indicating that the Pawtel's application design effectively meets user needs and has great potential to solve problems in finding and booking pet boarding services. So this study proves that the design thinking approach is able to produce products that are the right solution to the phenomenon raised.